Advanced Analysis of Time-lapse Seismic Data for CO2 Geosequestration Monitoring - Popik, Dmitry (Curtin University, 2019)
This thesis addresses challenges of land time-lapse (4D) surface seismic data analysis for monitoring of CO2 geosequstration. The approach includes development of an optimal seismic acquisition strategy, seismic forward modelling workflow, model-guided processing and imaging of the 4D seismic data for structural and quantitative interpretation. Successful onshore seismic monitoring is achieved using buried geophone array and purposefully designed processing flow with tracking of 4D signal and noise at each processing stage.